بناء اختبار لتقييم مستوى انتاجية وثبات الانتباه عند اطفال الرياض (Journal Of Educational and Psychological Researches, 2011)
Attention is one of the mental processes of knowledge that play an important role in the life of the individual in general and the child's life, in particular, the child relates to the external environment through its interaction with it, to achieve the adjustment with his environment and harmony with his community.Much ness and multiplicity of information sources make the child need to scan and exploration to provide the appropriate response by handling sensory stimuli involving the discovery of stimulus and receive it by sensory devices then pay attention to it and realizing and storing it in memory and restoring it in the next positions, The attention is essential for any learning process and there is no choice but the availability of high level of attention of learners from kindergarten to all school stages, so the current research aimed at building a test to assess the level of attention of children in the kindergarten of Baghdad departments on both sides Karkh and Rusafa for the academic year 2010/2011.According to the objective of this research, there was identification assess the level productivity& stability of attention, and there was a formulation of an item for each domain, where the number items of the productivity and stability (5), it has also been set beginning in front of each item (0, 1, 2) and the test is coupled with specific time, it was ( 15) seconds of each item of the test, the research sample  included (300) boys and girls, it have been extracted coefficient of difficulty and discriminatory power, coefficient of difficulty ranging between (0.540.79) The value of T (T-test) of the test items is between (8.359-10.997) , it has been shown, that all test items were featured at the level of sense (0,05) and the degree of freedom (160), and verifying the truth of test through the apparent validity and sincerity of construction by finding the correlation coefficient (Pearson) between the item and the domain that belongs to it and between the item and the total of test, as shown by the amount of persistence (0.85) in a re-test, and (0.92) in a manner to Alfakronbakh, and so it has been obtained to test consisting of (5) items formatted to apply to the children of kindergarten to assess the level productivity & stability of attention they have